Intercultural Competence Development:: A Journey of Self-Understanding and Perspective Transformation (Comparative & International Education Series, 2022)
In the summer of 2016, after a twenty-hour flight from Ho Chi Minh City, Vietnam, I landed in Canada to undertake my doctoral studies. My first doctoral course started three days after I arrived. As an international student, I encountered many challenges in navigating my life “in-between” cultures at the beginning of my doctoral journey. The story below depicts my feelings and emotions when I first received feedback on my writing from my doctoral supervisor, a Canadian Caucasian woman.